Heat Transfer Analysis of 3-D Viscoelastic Nanofluid Flow Over a Convectively Heated Porous Riga Plate with Cattaneo-Christov Double Flux - Loganathan, K.; Alessa, Nazek; Kayikci, Safak (Frontiers in Physics, 2021)
The impact of heat-absorbing viscoelastic nanofluidic flow along with a convectively heated porous Riga plate with Cattaneo-Christov double flux was analytically investigated. The Buongiorno model nanofluid was implemented with the diversity of Brownian motion and thermophoresis. Making use of the transformations; the PDE systems are altered into an ODE system. We use the homotopy analysis method to solve these systems analytically. The reaction of the apposite parameters on fluid velocity, fluid temperature, nanoparticle volume fraction skin friction coefficients (SFC), local Nusselt number and local Sherwood number are shown with vividly explicit details. It is found that the fluid velocities reflect a declining nature for the development of viscoelastic and porosity parameters. The liquid heat becomes rich when escalating the radiation parameter. In addition, the nanoparticle volume fraction displays a declining nature towards the higher amount of thermophoresis parameter, whereas the inverse trend was obtained for the Brownian motion parameter. We also found that the fluid temperature is increased in viscoelastic nanofluid compared to the viscous nanofluid. When we change the fluid nature from heat absorption to heat generation, the liquid temperature also rises. In addition, the fluid heat is suppressed when we change the flow medium from a stationary plate to a Riga plate for heat absorption/generation cases.